Reconfiguration Of The Role Of Madrasah Principals In Developing Teacher Personality Professionality - Limnawati Limnawati; Abdul Goffar; Abdul Haq As (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
Teacher personality professionalism is a fundamental dimension in improving the quality of education in madrasas. Madrasah principals have a strategic role in fostering, directing, and facilitating the strengthening of teachers' personality competencies. However, the dynamics of changes in educational policy require a reconfiguration of leadership roles to be more responsive and adaptive. This study aims to analyze the form of reconfiguration of the role of madrasah principals in fostering teacher personality professionalism at MTs Nurul Huda Al Banat Pelayan Kapongan. This study uses a qualitative approach with an empirical study design. Data were collected through in-depth interviews with madrasah principals, teachers, and education staff, observations of the coaching process, and document reviews. Data analysis was carried out through data reduction, data presentation, and interactive drawing of conclusions. The study shows that madrasah principals reconfigured their roles in three main aspects: (1) visionary leadership based on moral example; (2) strengthening a collaborative work climate through humanistic supervision and spiritual guidance; and (3) facilitating competency development through internal training and a continuous mentoring model. These changes have an impact on increasing teacher discipline, work ethic, and professional responsibility. Reconfiguring the role of the madrasah principal has been shown to contribute significantly to improving teacher professionalism. These findings recommend the development of a transformative leadership model based on role models and persuasive communication in madrasahs.